Pengaruh Product Knowledge, Literasi Keuangan Terhadap Keputusan Menabung Pada Bank BJB Makassar - Payuk, Ratna; Paranoan, Natalia; Sipi, Afian Dezi Sanda (Universitas Multi Data Palembang, 2025)
This research aims to examine the influence of product knowledge and financial literacy on customers' decisions to save at Bank BJB Makassar branch. The respondents in this study were 60 respondents who were customers who had savings at the Makassar branch of Bank BJB. By determining the sample size using the Roscoe formula. Furthermore, to measure the size of the research, a Likert scale was used with a test using the SPSS Version 26 program. Data analysis was carried out using multiple linear regression analysis, classical assumption tests, hypotheses, ANOVA tests and coefficient determination. The research results show that product knowledge and financial literacy have a significant effect on customers' decisions to save 30% at Bank BJB Makassar branch, with a value obtained of 0.306.